2011
DOI: 10.1557/opl.2011.1180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Interaction between Middle School Students and Materials Science and Engineering Researchers

Abstract: We, as education outreach providers at a research center, believe research scientists and engineers have much to contribute to science education. Our job is to design programs that allow our faculty and students to share their expertise and their stories to positively impact student learning and attitudes towards STEM fields. Is it possible to show that middle school students' interaction with scientists and engineers makes a positive difference in only one day? The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Several universities and science research institutes have reported on their experience with facilitating short, often one-day, interactions between researchers and school students. A prominent set of activities involves inviting school students to institutions to meet scientists and see laboratories 22 , 40 , 51 , 52 , or to attend open days comprising science demonstrations facilitated by scientists 53 . An alternative approach in the USA is the ‘Scientists In Classrooms’ (Fitzakerley, Michlin 54 where neuroscientists enter classrooms to provide a 40–60-minute talk about their work aiming to promote neuroscience literacy and positive attitudes towards neuroscience.…”
Section: International Experience Of School Engagementmentioning
confidence: 99%
“…Several universities and science research institutes have reported on their experience with facilitating short, often one-day, interactions between researchers and school students. A prominent set of activities involves inviting school students to institutions to meet scientists and see laboratories 22 , 40 , 51 , 52 , or to attend open days comprising science demonstrations facilitated by scientists 53 . An alternative approach in the USA is the ‘Scientists In Classrooms’ (Fitzakerley, Michlin 54 where neuroscientists enter classrooms to provide a 40–60-minute talk about their work aiming to promote neuroscience literacy and positive attitudes towards neuroscience.…”
Section: International Experience Of School Engagementmentioning
confidence: 99%
“…At the King David School in Australia a mentor program has positively influenced student attitudes toward STEM (Cerovac, 2013). A one day event for middle school students at the Princeton Centre for Complex Materials resulted in more positive attitudes toward science and scientists (Greco and Steinberg, 2011). So there are indications that targeted interventions have an effect on student attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%